2017
DOI: 10.17351/ests2017.42
|View full text |Cite
|
Sign up to set email alerts
|

From AIDS to Free Trade Agreements: Knowledge Activism in Thailand’s Movement for Access to Medicines

Gaelle Pascale Krikorian

Abstract: This article examines the movement for access to medicines in Thailand, a country that is a privileged site of observation of the new world order of pharmaceuticals and has been at the forefront in many international negotiations on intellectual property. The movement relies on the appropriation of knowledge and expertise about intellectual property laws, which developed in the context of the fight against HIV/AIDS. Treatment activism in Thailand is particularly vigorous and studying it allows us to grasp both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Our analysis shows that, since the WTO Doha Declaration on TRIPS and Public Health, access to medicines has become an established frame in many high, low, and middle-income countries and in global debates, which has influenced media reporting and public opinion. Furthermore, economic framing on the costs of medicines has been used in a supportive way in different contexts [ 10 , 23 , 37 , 71 , 80 ], benefiting from the dominant neoliberal paradigm. The studies demonstrate that evidence remains important, but must be translated so it is readily understood by policy actors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis shows that, since the WTO Doha Declaration on TRIPS and Public Health, access to medicines has become an established frame in many high, low, and middle-income countries and in global debates, which has influenced media reporting and public opinion. Furthermore, economic framing on the costs of medicines has been used in a supportive way in different contexts [ 10 , 23 , 37 , 71 , 80 ], benefiting from the dominant neoliberal paradigm. The studies demonstrate that evidence remains important, but must be translated so it is readily understood by policy actors.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies found that economic evidence (i.e. the costs and economic benefits) was used to elevate health goals – particularly in trade disputes regarding tobacco [ 67 , 68 ] and in supporting prioritisation of access to medicines in trade negotiations [ 10 , 23 , 37 , 71 , 80 ]. One study highlighted the generation of public opinion data commissioned by NGOs as influencing EU members of parliament not to support stringent IP measures in the ACTA agreement [ 73 ].…”
Section: Strategies and Conditions Enabling Elevation Of Health Goals...mentioning
confidence: 99%
See 2 more Smart Citations
“…The third topic that might be worth exploring is the circulation of certain models of patient activism developed mainly in Western Europe and North America to other regions of the world. Studies on transnational activism show how coalitions of patient associations or activist groups engage in the production and/or discussion of knowledge and expertise in different condition-areas (Krikorian 2017;Rabeharisoa and O'Donovan 2014). It might be interesting to extend studies on how these coalitions situate themselves vis-à-vis large non-governmental and philanthropic organizations which are particularly active in certain regions, and how these coalitions give shape to expertise drawn on concerned people's experiences (if they do).…”
mentioning
confidence: 99%